104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
Brad Geery presenting a $10,000 check from Fresno County Young Lawyers to Judge Dwayne Keyes for the Fresno County Law Library; Howard Watkins and Judy Soley Judge Keyes chaired the Board of Directors for the Law Library